PROBLEMS OF COLLABORATIVE LEARNING OF THE DIDACTIC UNIT OF INDUSTRIAL NETWORKS IN AN INSTITUTE IN CALLAO. CASE: CLASSROOM - Karina Elizabeth Torres Castillo, Edward Flores (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research is aimed at unveiling and analyzing the problem of collaborative learning of the didactic unit of industrial networks in an institute in Callao. Case: Classroom, which seeks to know the problem of collaborative learning of the didactic unit of industrial networks in students using the Classroom platform. Therefore, the present case study is of a qualitative interpretive approach, with a case study design, the techniques applied were student interviews, teacher interviews and documentary analysis, whose instruments were the student interview guide, interview guide to teachers and document analysis file. The unit of analysis was made up of nine students and three teachers. The triangulation of the discourses facilitated the obtaining of the emerging categories; Consequently, the most significant emerging categories were positive interdependence, individual and team responsibility, stimulating interaction, internal team management, and team evaluation. The conclusion of the study leads us to reveal the problem of collaborative learning using the Classroom platform. Therefore, it is necessary and important to give greater impetus to the work that is being done. It is proposed to carry out the proposal in order to complement the learning through the classroom platform of the fifth year high school students in the mathematics course, achieving interaction with different technological tools to strengthen the capacities and competencies in the students eliminating barriers of space and time.